A Conceptual Study on Anti-Poisonous Effect of Neeli Patradi Leham (International Journal of Ayurveda and Pharma Research, 2025)
Agada Tantra, as one of the eight principal branches of Ayurveda, focuses specifically on the management of Visha diseases, which encompass illnesses caused by toxins or poisons. Agada Tantra's role within Ayurveda is pivotal in addressing Visha diseases through a comprehensive approach that includes identification, prevention, diagnosis, and treatment. By blending ancient knowledge with modern insights, Agada Tantra continues to make significant contributions to the understanding and management of toxins and their impact on human health. Kerala indeed has a rich tradition in toxicology, rooted deeply in its ancient texts and practices within Ayurveda. The "Visha Vaidya Jyotsanika" is a renowned Malayalam text that focuses on Visha Chikitsa (toxicology) and offers valuable insights into various formulations and clinical practices. Neelipatradi leham is a formulation serves as a potent remedy mentioned in this text for counter acting poisons. This study emphasize on the components, preparation technique, indications, and efficacy of the formulation.